MATERI PENDIDIKAN DALAM Q.S. LUQMAN AYAT 12–19 DAN Q.S. AL-ISRA AYAT 23–25 - Abdul Wahab Syakhrani; Nor Laila, Nur Maulida Yulmi, Rahma, Rahmah Safitri (Adisam Publisher, 2025)
The educational material in Q.S. Luqman verses 12–19 and Q.S. Al-Isra verses 23–25 discusses the principles of Islamic education, which include the formation of monotheistic beliefs, the implementation of Sharia law, and the instilling of noble character from an early age through Luqman's direct advice to his son and the affirmation of the obligation to be devoted to one's parents. In these verses, education focuses on instilling faith in Allah, prohibiting polytheism, the importance of gratitude, teaching righteous deeds, strengthening noble character, and upholding social values such as respect, politeness, and empathy towards parents even in less than ideal circumstances. These two sets of verses also emphasise the urgency of moral and spiritual education and methods of character building through wise dialogue, loving warnings, and the involvement of role models in the family. The application of this integrated educational concept is believed to be able to address humanitarian issues and the challenges of modernisation.